ASPEK HUKUM ISLAM DALAM KITAB TA’LIM AL-MUTA’ALLIM KARYA BURHANUDDIN AL-ZARNUJI - Al Fakhri Zakirman; Nashiratun Nisa (ISLAMITSCH FAMILIERECHT JOURNAL, 2023)
Abstrak: Artikel ini bertujuan untuk mengetahui aspek hukum Islam dalam kitab Ta’lim al-Muta’allim. Kitab yang sangat fenomenal dalam dunia pendidikan Islam. Kajian ini menarik karena penulis kitab ini adalah Burhanuddin al-Zarnuji seorang ahli fiqh bermazhab hanafi. Padahal kitab Ta’lim al-Muta’allim tersebar di Indonesia yang notabene bermazhab syafi’i. metode yang peneliti gunakan adalah penelitian pustaka, peneliti mencoba membaca lebih dalam kitab Ta’lim al-Muta’allim lalu mengeluarkan poin-poin yang berkaitan dengan aspek hukum Islam dan keterpengaruhannya dari mazhab hanafi. Hasilnya peneliti menemukan ada empat poin yang disebut oleh al-Zarnuji secara eksplisit; hukum belajar ilmu haal, hukum belajar ilmu al-ahaayin, hukum memasang niat belajar dan hukum bersiwak. Secara umum al-Zarnuji dapat bersikap independen walau dengan kutipan guru-guru bermazhab hanafi dalam menjelaskan tanpa ada bias mazhab. Keywords: hukum islam; ta’lim al-muta’allim; al-Zarnuji Abstract This article aims to explore the Islamic legal aspects in the book "Ta’lim al-Muta’allim." This book is highly influential in the world of Islamic education. The study is intriguing because the author of the book is Burhanuddin al-Zarnuji, an expert in the Hanafi school of jurisprudence, while "Ta’lim al-Muta’allim" is widely disseminated in Indonesia, which is predominantly of the Shafi'i school. The research methodology employed is literature review, with the researcher delving into the content of "Ta’lim al-Muta’allim" to extract points related to Islamic legal aspects and the influence of the Hanafi school. The findings reveal four explicit points mentioned by al-Zarnuji: the legal aspects of learning the science of haal, the legal aspects of learning the science of al-ahaayin, the legal aspects of setting the intention to learn, and the legal aspects of using a tooth-stick (siwak). Overall, al-Zarnuji demonstrates an independent approach, even incorporating quotes from teachers of the Hanafi school in his explanations without showing any bias toward a particular school of thought. Keywords: Islamic law; Ta’lim al-Muta’allim; al-Zarnuji